Implantation of Squamous Cell Carcinoma in a Free Flap Donor Site. (September 2020) - Pichardo, Priscilla; Purdy, Nicholas; Haugen, Thorsen
Introduction: It is well known that malignant cells can be implanted at distant donor sites due to iatrogenic surgical contamination. Only a small number of reports, however, have been published describing this. Case Presentation: We present a case of oral cavity Squamous Cell Carcinoma (SCC) reconstructed with a radial forearm free flap in which SCC developed in the subcutaneous tissues beneath the donor incision site 6 months after surgery. Management: The implanted tumor was excised and the field was subsequently treated with radiation. The patient remains disease-free on follow-up. Discussion: We present the second report of tumor implanted in a free flap donor site. Additionally, we discuss the risks of tumor implantation, review the literature, and make recommendations to avoid this complication.